La importancia de la asociatividad para el desarrollo - Guerrero Bejarano, María Auxiliadora (2016)
The following research paper presents a comprehensive overview of the factors involved in the community associations processes, and its relationship and importance to the environment in which it is applied, in order to propose a strategy to enhance partnership in the under the community development. This research was able to conclude the importance of the complementary relationship between economic and non-economic factors involved in the processes of community association and also managed to secure a comprehensive strategy to stimulate both factors for economic and social development our object of study, the municipality of San Rafael in the Province of Santa Elena, Ecuador.